Responses of urban crows to con- and hetero-specic alarm calls in predator and non-predator zoo enclosures. - Bílá, Kateřina (Jihočeská univerzita, 2017)
I investigated if urban crows respond to con- and heterospecific alarm signals in predator and non-predator contexts in enclosures in the ZOO of Vienna. Crows responded strongly to the crow and also jackdaw alarms in both types of contexts, but also responded to the singing of great tit (control) in the predator context. This suggests that crows are aware of the danger the wolf and bear represent but are generally very cautious at the exotic Zoo animals.
Responses of urban crows to con- and hetero-specic alarm calls in predator and non-predator zoo enclosures.
Keywords: varovné hlasy; vrána obecná; konspecifické signály; heterospecifické signály; komunikace; interspecifické signály; alarm call; carrion crow; conspecific signal; hetero-specific signal; communication; predator avoidance; inter-specific signalling